Socio-Economic and Demographic Determinants of Fertility in Azerbaijan: the Role of Son Preference - Kanan V. Salayev; Natalia M. Kalmykova (Население и экономика)
The paper analyses fertility and reproductive behaviour in Azerbaijan with a focus on the impact of socio-economic and cultural factors. Particular attention is paid to the impact of mothers’ level of education, economic wealth well-being of families and cultural preference for sons. The study is based on the data from the Multiple Indicator Cluster Survey (MICS) 2000, 2006 Azerbaijan Demographic and Health Survey (AzDHS 2006), and the Republic of Azerbaijan’s Ministry of Labour and Social Protection of Population (MLSP) survey for 2015-2017. Econometric methods allowed to identify the relationship between having many children in a family and such factors as mother’s higher education, level of family wealth and son preference.